Extraction and antimicrobial evaluation of capsaicinóides from three peppers varieties of genus Capsicum - Santos, Vidiany Aparecida Queiroz; Nunes, Karin Martins; Cruz, Crispin Humberto Garcia (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
Capsicum sp. peppers besides to conferring a distinct flavor in foods have bioactive potential such as antimicrobial capacity against some deteriorating and pathogenic microorganisms, which is interesting to point view hygienic-sanitary. In this work, antimicrobial potential of caipsaicinoids obtained of Capsicum frutescens (malagueta), C. baccatum L. var. praetermissum (cumari) and C. baccatum (dedo-de-moça) against different microorganisms were carried out. Peppers were crushed and added in absolute ethanol, producing raw extract (hydroalcoholic extract), which was fractionated with three organic solvents of different polarities (ethyl acetate, chloroform and hexane). Antimicrobial activity of pepper extracts was determined by disk diffusion method. Gram negative bacteria (Escherichia coli and Salmonella enterica Thyphimurium) and filamentous fungi were the most sensitive microorganisms to pepper extracts tested. Gram-positive bacteria were resistant to all extracts evaluated. Chloroform and ethyl acetate pepper extracts were the most efficient against all microorganisms. Among the three peppers varieties tested, Capsicum frutescens pepper showed greater antimicrobial potential, followed by C. baccatum L. var. praetermissum and C. baccatum L